Quality of Life of Post-stroke Patients - Bártlová, Sylva; Šedová, Lenka; Havierniková, Lucie; Hudáčková, Andrea; Dolák, František; Sadílek, Petr (Zdravstveno varstvo, 2022)
Introduction: Stroke is a disease whose consequences have a considerable impact on the quality of the patient's life. It is a widespread disease that has a disabling impact on life and, in addition to physical changes, brings about a number of psychological and cognitive processes. Goal: The goal of the study was to identify and describe the quality of life of post-stroke patients. Methodology: The study design was quantitative. A questionnaire of the authors' own design and the SF-36 questionnaire were used to obtain the data. Results: Significant differences in patient quality of life were identified in relation to patient gender. Moreover, the quality of life in all individual SF-36 dimensions, except for mental health, deteriorated with age. With regard to occupational placement, employed respondents gave the highest evaluation of quality of life according to SF-36 and old-age pensioners the lowest. The analysis shows that quality of life in individual dimensions is positively influenced by respondents' higher education. The evaluation in individual dimensions improves with the time that has passed since the stroke. Conclusion: The quality of life of post-stroke patients deteriorates with age. The deteriorating level of patient quality of life in older age requires programmes that include assessments and interventions that lead to the treatment of these patients.